Convolutions of Harmonic Mappings Convex in the Horizontal Direction - Serkan Çakmak; Elif Yaşar; Sibel Yalçın (Journal of Function Spaces)
In this paper, we establish some results concerning the convolutions of harmonic mappings convex in the horizontal direction with harmonic vertical strip mappings. Furthermore, we provide examples illustrated graphically with the help of Maple to illuminate the results.